Accuracy of lung and diaphragm ultrasound in predicting successful extubation in extremely preterm infants: A prospective observational study. Issue 2 (11th November 2022) - Mohsen, Nada; Nasef, Nehad; Ghanem, Mohab; Yeung, Telford; Deekonda, Veena; Ma, Carmen; Kajal, Dilkash; Baczynski, Michelle; Jain, Amish; Mohamed, Adel
Abstract: Objective: Chest ultrasound has emerged as a promising tool in predicting extubation readiness in adults and children, yet its utility in preterm infants is lacking. Our aim was to assess the utility of lung ultrasound severity score (LUSS) and diaphragmatic function in predicting extubation readiness in extremely preterm infants. Study Design: In this prospective cohort study, preterm infants < 28 weeks gestational age (GA) who received invasive mechanical ventilation for ≥12 h were enrolled. Chest ultrasound was performed before extubation. The primary outcome was lung ultrasound accuracy for predicting successful extubation at 3 days. Descriptive statistics and logistic regression were done using SPSS version 22. Results: We enrolled 45 infants, of whom 36 (80%) were successfully extubated. GA and postmenstrual age (PMA) at extubation were significantly higher in the successful group. The LUSS was significantly lower in the successful group compared to failed group (11.9 ± 3.2 vs. 19.1 ± 3.1 p  < 0.001). The two groups had no statistically significant difference in diaphragmatic excursion or diaphragmatic thickness fraction. Logistic regression analysis controlling for GA and PMA at extubation showed LUSS was an independent predictor for successful extubation (odd ratio 0.46, 95% confidence interval [0.23–0.9], p  = 0.02). The area under the receiver operating characteristic curve was 0.95 ( p  ˂ 0.001) for LUSS, and a cut‐off value of ≥15 had 95% sensitivity and 85% specificity in detecting extubation failure. Conclusion: In extremely preterm infants, lung ultrasound has good accuracy for predicting successful extubation. However, diaphragmatic measurements were not reliable predictors.